A Crisis-Responsive Framework for Medical Device Development Applied to the COVID-19 Pandemic - Antonini, Marc-Joseph; Plana, Deborah; Srinivasan, Shriya; Atta, Lyla; Achanta, Aditya; Yang, Helen; Cramer, Avilash K.; Freake, Jacob; Sinha, Michael S.; Yu, Sherry H.; LeBoeuf, Nicole R.; Linville-Engler, Ben; et al. (Frontiers in Digital Health, 2021)
The disruption of conventional manufacturing, supply, and distribution channels during the 2020 COVID-19 pandemic has caused widespread shortages in personal protective equipment (PPE) and other medical supplies. These shortages have catalyzed local efforts to use nontraditional, rapid manufacturing to meet urgent healthcare needs. Here we present a crisis-responsive design framework designed to assist with product development under pandemic conditions. The framework emphasizes stakeholder engagement, comprehensive but efficient needs assessment, rapid manufacturing, and modified product testing to enable accelerated development of healthcare products. We contrast this framework with traditional medical device manufacturing that proceeds at a more deliberate pace, discuss strengths and weakness of pandemic-response fabrication, and consider relevant regulatory policies. We highlight the use of the crisis-responsive framework in a case study of face shield design and production for a large US academic hospital. Finally, we make recommendations aimed at improving future resilience to pandemics and healthcare emergencies. These include continued development of open source designs suitable for rapid manufacturing, education of maker communities and hospital administrators about 3D printing medical devices, and changes in regulatory policy that help strike a balance between quality and innovation.